2014 IEEE International Congress on Big Data 2014
DOI: 10.1109/bigdata.congress.2014.66
|View full text |Cite
|
Sign up to set email alerts
|

ADAM - A Database and Information Retrieval System for Big Multimedia Collections

Abstract: The past decade has seen the rapid proliferation of low-priced devices for recording image, audio and video data in nearly unlimited quantity. Multimedia is Big Data, not only in terms of their volume, but also with respect to their heterogeneous nature. This also includes the variety of the queries to be executed. Current approaches for searching in big multimedia collections mainly rely on keywords. However, manually annotating every single object in a large collection is not feasible. Therefore, content-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…ADAM uses PostgreSQL and comes with the Vector Approximation-File [14] indexing and k nearest neighbor search. The evaluation of ADAM has shown that it is able to handle big multimedia collections of multiple million objects and keep the retrieval time well below a few seconds (e.g., for 14 million elements each storing 144 dimensions, ADAM returns results on average in 0.55 seconds for the 100 most similar objects [5]). …”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…ADAM uses PostgreSQL and comes with the Vector Approximation-File [14] indexing and k nearest neighbor search. The evaluation of ADAM has shown that it is able to handle big multimedia collections of multiple million objects and keep the retrieval time well below a few seconds (e.g., for 14 million elements each storing 144 dimensions, ADAM returns results on average in 0.55 seconds for the 100 most similar objects [5]). …”
Section: Databasementioning
confidence: 99%
“…IMOTION is based on the distributed storage system ADAM [5] that allows to easily manage, organise, and query multimedia objects, i.e., the corresponding structured metadata, as well as the extracted high-dimensional feature vectors. ADAM uses PostgreSQL and comes with the Vector Approximation-File [14] indexing and k nearest neighbor search.…”
Section: Databasementioning
confidence: 99%
“…In [22], author describe that the data is not big in terms of their volume but also include the queries that are performed to access that data. There are many strategies through which we can search data using different keywords.…”
Section: A Research Paper Summariesmentioning
confidence: 99%
“…All feature vectors along with meta-data are stored in the database and information retrieval system ADAM [16] which is built upon PostgreSQL and is capable of performing efficient vector space retrieval together with Boolean retrieval.…”
Section: Scoring Video Search Tools In Vbs2015 41 Imotionmentioning
confidence: 99%